Penerapan Hukum Perdata Internasional dalam Sengketa Merek Lintas Batas: Studi Kasus IKEA (PT Ratania Khatulistiwa Indonesia vs. IKEA Swedia) - Nugroho, Lucky Dafira; Maltufah, Siti; Kholis, Kholis (AHKAM, 2025)
This study examines the application of Private International Law (PIL) in resolving cross-border trademark disputes, focusing on the case of IKEA Sweden versus PT Ratania Khatulistiwa Indonesia. The dispute arose due to differing legal principles: Indonesia’s legal system adheres to the first to file principle, while international systems recognize the first use principle and the protection of well-known trademarks. The Supreme Court of the Republic of Indonesia ruled in favor of the domestic party, concluding that IKEA Sweden did not meet the criteria for active use of the trademark in Indonesia. This study employs a normative legal approach using a descriptive-analytical method through literature review. The analysis is based on primary, secondary, and tertiary legal materials and incorporates statutory, conceptual, and case approaches, encompassing the principles of jurisdiction, choice of law, and recognition and enforcement of foreign judgments. The findings reveal that the Indonesian legal system has not fully accommodated PIL principles, particularly regarding the protection of well-known trademarks. The lack of harmony between the principle of good faith and the principle of territoriality has resulted in legal uncertainty, especially for foreign investors. Moreover, the recognition and enforcement mechanism for foreign judgments remains ineffective, potentially leading to conflicting rulings in multi-forum litigation. This study concludes that reformulating the national legal system in alignment with PIL principles and international standards is crucial to enhancing trademark protection and fostering legal certainty in support of a globally competitive investment climate.